Dresmo Village: Local Traditions and the Influence of Islam - Badrya, Mas; Ghazalian , Marcelina; Mubarok , Ahmad Syafiul (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to analyze the formation of local traditions in Dresmo Village, Surabaya, and the influence of Islamic teachings in preserving and modifying these traditions. Dresmo Village is known for its rich local traditions and strong Islamic practices. Using a qualitative approach, this research examines the process of acculturation between local culture and Islam, based on acculturation theory which highlights changes resulting from cultural interaction. The findings reveal a unique fusion between customs and Islamic values, as seen in practices such as kenduri and tahlilan, which have been modified to align with religious teachings without losing their cultural meaning. The role of religious and community leaders is crucial in maintaining this balance. Cultural adaptation theory supports the finding that the community is capable of preserving traditional identity while simultaneously integrating religious values into daily life. Despite the challenges posed by modernization, the Dresmo community has successfully maintained harmony between tradition and religion.